The establishment and application of isothermal cross‐priming amplification techniques in detecting penaeid shrimp white spot syndrome virus. (1st August 2014) - Yang, H.‐L.; Huang, J.; Yang, B.; Liu, F.; Zhang, Q.‐L.
Abstract: White spot syndrome virus (WSSV) is one of the main pathogens seriously threatening penaeid shrimp farming in the world. This study designed and synthesized five specific primers based on the conserved sequences of WSSV genome, optimized the reaction system and conditions, and finally established a cross‐priming amplification (CPA)‐based detection method for WSSV (WSSV‐CPA). The results indicated that the optimized reaction temperature and time of WSSV‐CPA were 63°C and 60 min, respectively. The detection limit of the WSSV‐CPA assay was as low as 10 copies μ l −1 and shared same sensitivity with the WSSV‐qPCR assay. Due to dispensing with expensive thermal cycler, time‐ and cost‐saving, and ease of use in field, it is anticipated that the WSSV‐CPA method developed in this study will be instrumental for the diagnosis and surveillance of WSSV. Significance and Impact of the Study: White spot syndrome, caused by white spot syndrome virus (WSSV), is the major disease threatening the shrimp aquaculture industry and leads to tens of billion dollars of economic losses in the world each year. This study established a CPA‐based method for detecting WSSV, which is rapid, sensitive and specific. It is anticipated that this novel assay will be instrumental for diagnosis and surveillance of WSSV.